Diluted Ionic Liquid Electrolyte‐Assisted Stable Cycling of Small Molecular Organics. Issue 23 (9th December 2021) - Xu, Ting; Qin, Jian; Liu, Yutao; Lan, Qing; Zhao, Yali; Song, Zhiping; Zhan, Hui
Abstract: Small‐molecular organic materials with high capacity and fast reaction kinetics have gained increasing attention, but they are greatly bothered by the dissolution issue. Unlike the mainstream approaches of material processing, herein, an electrolyte strategy has been proposed to address the dissolution loss of anhydride materials. With the assistance of binary diluent, longer than 1000 times of stable cycling have been realized by 3, 4, 9, 10‐perylenetetracarboxylic dianhydride (PTCDA) in ionic liquid electrolyte. Further investigation indicates that the diluent strategy has enabled the same stable cycling under high temperature or on high‐loading electrodes, and additionally, its effectiveness has been proved on other small‐molecular organics. Abstract : Overcoming dissolution issues : A binary‐diluent localized concentration ionic liquid (LCIL) electrolyte was proposed for small organics to address their dissolution issue. Owing to the elaborately designed electrolyte composition, over 1000 times cycling without appreciable capacity decline at room temperature and high temperature was exhibited by the Li/anhydride cell.